Chondroitin sulfate epitope (WF6) and hyaluronic acid as serum markers of cartilage degeneration in patients following anterior cruciate ligament injury - Dumnoensun Pruksakorn (2018)
Serum chondroitin sulfate epitope (WF6) and hyaluronic acid (HA) levels were determined to be of clinical relevance to an anterior cruciate ligament (ACL) injury. This cross-sectional study recruited participants from two distinct groups. Group A was comprised of 74 healthy controls, and group B consisted of 33 ACL injury patients. Serum samples were taken and assayed by a competitive immunoassay with monoclonal antibody WF6. Serum HA was also determined by an ELISA-based assay using biotinylated HA-binding proteins. Both groups A and B shared similar values of age, body mass index, white blood cell count and percentage of polymorphonuclear cells. ESR levels were also shown to be within normal limits. The serum WF6 epitope levels of group B were significantly higher than those of group A, whereas serum HA levels were not different between the two groups. The serum WF6 epitope level is more sensitive to changes in articular cartilage due to a non-inflammatory instability condition than the serum HA level, and should prove to be one of the most promising assays for early post-traumatic arthritis detection. © 2008 Sports Medicine Australia.